FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PETANI KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT, TERHADAP PEMBIAYAAN BANK SYARIAH - Nurapriajul Kurnaen, Muhamad Reza; Trihantana, Rully; Kusumaningrum, Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Most of the Indonesian people carry out agricultural sector activities by relying on their own capital or funds. Lack of availability of capital for the agricultural sector will lead to a decrease in agricultural output. Therefore, the best alternative is the provision of capital in the form of Islamic bank financing for farmers in carrying out farming activities. The purpose of this study was to analyze the factors that influence the interest of rice farmers in Pamijahan District (Pamijahan Village, Cibunian Village, and Ciasihan Village) towards financing in Islamic banks with quantitative methods, primary data obtained from the results of distributing questionnaires to a sample of 78 respondents. The results showed 5 independent variables consisting of promotion, knowledge, income, education level, religiosity, variables that can affect farmers' interest, namely the knowledge variable with a tcount value of 2,945 > ttable 1,991. and the sig value is 0.004 < 0.05. Meanwhile, simultaneously the independent variables consisting of promotion, knowledge, income, education level, and religiosity have a positive effect on Islamic financing with a value of fcount > ftable (4.723 > 2.34) and a sig value of 0.001 < 0.05.